Three-Dimensional Hemodynamics in the Human Pulmonary Arteries Under Resting and Exercise Conditions - Tang, Beverly T; Fonte, Tim A; Chan, Frandics P; Tsao, Philip S; Feinstein, Jeffrey A; Taylor, Charles A (Annals of biomedical engineering, 2011)
The biomechanical forces associated with blood flow have been shown to play a role in pulmonary vascular cell health and disease. Therefore, the quantification of human pulmonary artery hemodynamic conditions under resting and exercise states can be useful in investigating the physiology of disease development and treatment outcomes. In this study, a combined magnetic resonance imaging and computational fluid dynamics approach was used to quantify pulsatile flow fields, wall shear stress (WSS), oscillations in WSS (OSI), and energy efficiency in six subject-specific models of the human pulmonary vasculature with high spatial and temporal resolution. Averaging over all subjects, WSS was found to increase from 19.8 ± 4.0 to 51.8 ± 6.7 dynes/cm², and OSI was found to decrease from 0.094 ± 0.016 to 0.081 ± 0.015 in the proximal pulmonary arteries between rest and exercise conditions (p < 0.05). These findings demonstrate the localized, biomechanical effects of exercise. Furthermore, an average decrease of 10% in energy efficiency was noted between rest and exercise. These data indicate the amount of energy dissipation that typically occurs with exercise and may be useful in future surgical planning applications.